Orders of Edward Montagu, Earl of Sandwich - Sandwich, Edward Montagu, Earl of, 1625-1672.
Two orders of Sandwich as admiral of the narrow seas: one (1660 October 6) authorizing funds for payment to Royal Navy officers and crew and the other (1660 December 16) requesting that a vessel be outfitted to transport Henry Jermyn, Earl of St. Albans, to France.
British naval officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: St. Albans, Henry Jermyn, -- Earl of, -- approximately 1604-1684.; England and Wales. -- Admiralty; England and Wales. -- Royal Navy; France -- Foreign affairs -- Great Britain; Great Britain -- Foreign affairs -- France; Naval officers, British